Caracterização por DNA metabarcoding da biodiversidade de ambientes neotropicais : investigação das comunidades presentes em fitotelmos de bromélias e sedimentos marinhos - Simão, Taiz Leonor Lopes (2016)
This project applied the DNA metabarcoding technique, which consists of a large-scale identification of the biodiversity present in a given community (through the total DNA sequencing without the need for isolation and laboratory cultivation) in two underexplored Brazilian environments with high biological diversity. The first is a typical Neotropical microenvironment, called bromeliad phytotelm, which is formed by the accumulation of water and debris among the leaves of these plants. The bromeliads investigated in this study were sampled in areas of dense ombrophilus forest and mixed ombrophilus forest in southern Brazil (located at the “Pro-Mata” Research Center), and belonged to the species Aechmea gamosepala Wittmack, Vriesea friburgensis Mez and Vriesea platynema Gaud. The collection comprised multiple individuals per species and also multiple samples (different tanks) from the same individual, making it possible to assess the complexity of the variation in these communities. The second environment consists of marine sediments collected in the Rio Grande Cone (located in southeastern Brazil, in the offshore portion of the Pelotas Basin), at depths of down to 18 meters below the seafloor. The samples originated from four different areas, with different geochemical characteristics and strong indications of the presence of chemosynthetic communities. This study demonstrated the presence of high biodiversity in both environments. We identified 30 prokaryotic phyla and 67 eukaryotic phyla in bromeliad phytotelmata, which seem to include both endemic organisms of this peculiar environment and organisms with ubiquitous distribution, common in freshwater or soil habitats. An interesting feature is that, in some cases, samples from different tanks of the same individual are more similar to tanks of other individuals (and even from other species) than between them. Thus, our results suggest that each bromeliad tank acts as an isolated body of water, where the effects of predation, competition and stochastic events such as wind-borne particles, fecal pellets and liquid excretions of terrestrial animals, dead leaves and animals can largely drive the community composition. Concerning the marine sediments, we observed the presence of 58 prokaryotic phyla, many of which are present in other chemosynthetic communities. Among these organisms were identified anaerobic methanotrophic archaeal groups and their syntrophic partners (sulfate-reducing bacteria), which together form a consortium with a significant role in the anaerobic oxidation of methane, a very important process that controls the emission of this greenhouse gas into the atmosphere. Statistical analysis performed in both studies sought to describe patterns of diversity of these communities at different spatial scales and to interpret them in the light of current knowledge about these environments. Overall, the results obtained in this thesis reveal in detail the complexity of these communities, opening new ways for further studies focusing on the processes that control their spatio-temporal dynamics.